OPPORTUNITIES OF INTEGRATED NUTRIENT MANAGEMENT IN KANCHANPUR, NEPAL - JANAK PANT; PRAVA DAWADI (Innovare Journal of Agricultural Sciences, 2024)
Objectives: The study of opportunities for integrated nutrient management lacking in the Kanchanpur district. Hence, an experiment was carried out to study different combinations of fertilizers to determine suitable integration of fertilizers during November 2023–September 2024. Methods: The experiment was conducted in a randomized complete block design. Paddy and vegetable (cauliflower) crops were selected for the 14 research. The sources of fertilizers applied in the research were FYM (Farmyard Manure), poultry manure, vermicompost, green manures, and chemical fertilizer. Six combinations of treatments were prepared, namely (i) T1: 100% N from the recommended dose of chemical fertilizer (RDF) (RDF:200:120:80 NPK kg/ha), (ii) T2: 50% N from RDF+50% N from farmyard manure (FYM), (iii) T3: 50% N from RDF+50% N from poultry manure (PM), (iv) T4: 50% N from RDF+50% N from vermicompost (VC), (v) T5: 50% N from RDF+50% N from green manure (GM), and (vi) T6: 20% N from 17 RDF+20% N from FYM+20% N from PM+20% from VC+20% N from GM. Results: Combinations of 50% N from RDF+50% N from FYM, 50% N from RDF+50% N from PM, 50% N from RDF+50% N from VC, and 50% N from RDF+50% N from GM provided almost similar results in plant parameters, root, and soil property. Sole application of 100% N from the RDF resulted with the lowest effect in plant and soil attributes. Conclusion: The integration of 20% N from RDF+20% N from FYM+20% N from PM+20% from VC+20% N from GM was found to be the most effective nutrient management opportunity in the district.